KAJIAN PENGEMBANGAN TEMPAT PELELANGAN IKAN (TPI) DI SENTRA KAWASAN PELABUHAN PERIKANAN MUARA KINTAP KABUPATEN TANAH LAUT PROVINSI KALIMANTAN SELATAN - Akhmad Syarwani; Idiannor Mahyudin; Emmy Sri Mahreda (Universitas Lambung Mangkurat, 2016)
The potential Fish Auction Place in the fish port of Muara Kintap is expected to become the center of economic growth and development of fisheries. The existence of the facility is an input to the process of the function implementation in Fish Auction Place which condition is related to its availability and number in the fish port. The facilities which are managed optimally will produce the optimum output anyway. This study aimed to identify the presence of TPI in the central area of the Muara Kintap in Kecamatan Tanah Laut which has the potential to be developed. This study uses descriptive qualitative research and literature survey. Based on the survey results, it was revealed that the condition of Fish Auction Place (TPI) in the fish port of Muara Kintap in Kecamatan Tanah Laut did not implement a pure auction, it was due to the basic facilities, unwell maintained functional and supporting tools, and also due to the collaboration of some merchants in controlling prices. Several attempts to optimize Fish Auction Place (TPI) including the addition of supporting facilities, such as clean water, cool boxes, scales and carts/baskets as well as banks as partners in financial institutions to access capitals for a business group of fishermen. The comfortable condition of loading and unloading activities, as well as sanitation and hygiene, really needs to be fulfilled, including the revitalization of the fish fleet. Ideally, in every region of fishery activities in a fishermen concentration area, a fish port should be built, or at least fish hauling with clean Fish Auction Unit, to meet the requirements of the integrated quality program so that the selling prices of fish caught by fishermen con be rewarded appropriately. SWOT analysis results indicated that strategy chosen was the S - O (Strengths – Opportunities) which utilized all power of Muara Kintap Fish Port to take advantage of development opportunities as much as possible.